Seroprevalence of Toxoplasma Gondii in Sheep, Cattle and Horses in Urmia North-West of Iran - A Akaberi; S Sedeghi; S Raeghi (Iranian Journal of Parasitology, 2011)
Background: Toxoplasma gondii is a zoonotic protozoan parasite found worldwide and responsible for major economic losses in most classes of livestock. This study was aimed to determine the prevalence of T. gondii infection in sheep, cattle and horses in Urmia, north-west of Iran, using MAT.Methods: Blood samples of 276 livestock and 26 horses were collected from July 2009 till April 2010. The data were analyzed by the Chi-square, Fisher's Exact and Cochran's and Mantel-Haenszel Tests. The level of significance was set at P < 0.05.Results: Thirty-three (21.1%) sheep, 2 (1.6%) cattle and 3 (11.5%) horses were seropositive to T. gondii. Analysis showed that sheep were 15 times more likely to be seropositive comparing to cattle also 2 times more likely to be seropositive than horses.Conclusion: This study showed seroprevalence of equine T. gondii infection with a considerable rate in sheep in Urmia, northwest of Iran. More comprehensive studies on livestock toxoplasmosis are required for further analysis of the parasite reservoir for human infection.